Correction: Publisher Correction: Wave kinetics of random fibre lasers - D. V. Churkin (Nature Portfolio, 2018)
Nature Communications 6: Article number: 6214 (2015); Published 3 February 2015; Updated 25 May 2018 The original HTML version of this Article had an incorrect volume number of 2; it should have been 6. This has now been corrected in the HTML; the PDF version of the Article was correct from the timeof publication.